Engaging with Indigenous Water Realities: Agricultural Cycle Rituals and Oral Tradition - Aguilera Lara, Jahzeel; Camou-Guerrero, Andrés; Montoya, David; Casas, Alejandro; Toledo, Victor M (Ethnobiology and Conservation, 2023)
The Nahua communities in the Central Highlands of Guerrero have a ritual-agricultural cycle closely related to seasonality, environmental processes, agriculture, and landscape. The most important celebrations in the region are those asking for a good rainy season, for the rain to end, and to thank for the harvest. Building upon the ethnoecological framework, the article explores ritual-agricultural practices and the water realities these practices make, as well as their implications in the conservation and management of water.